The public sector as an adapter for digital innovation - Agafonova Margarita; Bautina Elena; Poryadina Vera; Likhacheva Tatyana (E3S Web of Conferences, 2021)
The paper attempts to study the theoretical aspects of digitalization of the economy. Analysis of the current level of development of the digital economy in Russia is presented. An assessment of the current state of digital transformation of the public sector is made. Potential opportunities and threats from the digital economy in relation to the public sector are identified. The prospects for the digital transformation of the public sector economy are identified. The theoretical and practical significance of the work is determined by the novelty of the conclusions and a comprehensive study of the problem with the subsequent systematization of the data. The content of the paper, its main conclusions and provisions can be used both for further in-depth study of digital solutions and their impact on the economy, and for direct guidance on the implementation of digital technologies in the economy.